2023
DOI: 10.3390/agronomy13030649
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nutrient and Antioxidant Profile of High Lycopene Variety with hp Genes and Ordinary Variety of Tomato under Organic Conditions

Abstract: Organic tomato cultivation is growing all over the world due to its healthy functional properties and environmental concerns. Recently, some new varieties with increased functional properties, particularly high lycopene, have been developed. However, few were assessed under organic farming systems. The objective of this study was to evaluate physico-chemical properties and the main bioactive compound contents, as well as lipophilic, hydrophilic and total radical scavenging activities of a recently developed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
1
1
Order By: Relevance
“…The data were similar to those formerly found in organic tomatoes grown in Tunisia, with 123.8, 81.5, and 205.3 µM Trolox/100 g fw for LRSA, HRSA and TRSA, respectively [37]. The results of the current research were higher than those recently reported for the activities of LRSA, HRSA, and TRSA in the organically grown Nemador variety, with 107.7, 74.8, and 182.5 µM Trolox/100 g fw, respectively [47]. This is probably due to genotypic differences.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The data were similar to those formerly found in organic tomatoes grown in Tunisia, with 123.8, 81.5, and 205.3 µM Trolox/100 g fw for LRSA, HRSA and TRSA, respectively [37]. The results of the current research were higher than those recently reported for the activities of LRSA, HRSA, and TRSA in the organically grown Nemador variety, with 107.7, 74.8, and 182.5 µM Trolox/100 g fw, respectively [47]. This is probably due to genotypic differences.…”
Section: Discussioncontrasting
confidence: 78%
“…Comparable values for α-tocopherol, between 14.3 and 26.8 µg/g fw, in tomatoes grown under organic management were found by Fracchiolla et al [39]. The results were in the range of those found recently by Romdhane et al [47], who noted α-tocopherol values that varied from 17.0 to 27.7 mg/kg fw in organically grown Nemador and high lycopene tomato varieties, respectively. The γ-tocopherol content was only detected in the new tomato germplasm line OSTGL, with 0.28 mg/kg fw.…”
Section: Discussionsupporting
confidence: 68%
“…The study found that using vermicompost significantly increased tomato fruit quality, and enhanced soil health, indicating its positive impact on tomato production [44]. The high lycopene content is also correlated with suitable yield, fruit weight, titratable acidity, °Brix, pulp color, and significantly higher lycopene, β-carotene, and vitamin C contents [45]. Vermicompost, derived from cow dung and farm waste, supports essential nutrients, enhancing plant growth, photosynthesis, and chlorophyll contents [46].…”
Section: Impact On Soil Healthmentioning
confidence: 86%
“…The tomato plays a key part in a variety of food products, from juice to soups, from canned treats to powerful sauces (Romdhane et al, 2023;Wu and Nelson, 2023). This is because the tomato's organic germplasm is enhanced by the presence of phenols, flavonoids, vitamin C, tocopherols, and antioxidants.…”
Section: Introductionmentioning
confidence: 99%